PENGARUH DIMENSI GLOBALISASI TERHADAP PERDAGANGAN INTERNASIONAL DI BEBERAPA NEGARA ASIA TENGGARA - Safitri; I Made Endra Kartika Yudha; I Nyoman Mahaendra Yasa; I Nyoman Wahyu Widiana (Berajah Journal, 2026)
International trade is an important indicator of a country’s economic openness and integration into the global system, where Southeast Asian countries such as Indonesia, Malaysia, Myanmar, and Thailand exhibit varying trade dynamics influenced by economic, social, and political globalization. This study aims to analyze the impact of these three dimensions of globalization on international trade during the 1980–2023 period using panel data regression with the Fixed Effect Model at a five percent significance level. The results show that, simultaneously, all dimensions of globalization have a significant effect on international trade. However, partially, economic globalization has a negative and significant effect, while social and political globalization have positive and significant effects. This indicates that economic openness without adequate domestic readiness can hinder trade performance, whereas social connectivity and political cooperation can enhance trade activities. Therefore, appropriate policies are needed to optimize the benefits of globalization while minimizing risks such as import dependency, global commodity price volatility, and low export diversification.